Test for Chlorine Content (Cl2) in Rice at Manonda Inpres Market, Palu - Nur Rismawati (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2021)
This study aims to determine the chlorine content (Cl2) in rice at the Manonda Inpres Market in Palu by conducting laboratory tests. This type of research is a descriptive study with an observational approach. This research describes the examination of chlorine content (Cl2) in rice at the Manonda Inpres Market in Palu through laboratory tests. The object of this research is the total of 15 rice merchandise samples scattered in the Manonda Inpres Market, Palu. The results showed that the 15 rice samples were declared non-reactive, which means that all samples did not contain chlorine (Cl2). This study suggests that health agencies are expected to carry out health and food safety checks of hazardous food additives, in particular routine checks of chlorine (Cl2) content in rice.